EKSISTENSI METODE JIBRIL DALAM BINA BACA AL-QUR’AN SANTRI - Luqman Hakim (Jurnal Studi Pesantren, 2022)
The Qur'an is the word of Allah, which was revealed to the Prophet Muhammad through the Angel Gabriel, which is written in the Mushaf and reached us by oral route, was read by him to his companions, and continues to us in a mutawatir way, reading it is worship. which begins with Surah-Fatihah and ends with Surah an-Nas. Al-Qur’an is a holy book for Muslims all over the world, as well as a guide for all mankind. Whoever speaks with the Qur'an, then he speaks the truth. So whoever turns away from the Qur'an, and turns to other directions, he will surely go astray. Gabriel's method is needed to accelerate the process of learning to read the Qur’an correctly, tajwid and fulfill other reading rules. The biggest problem for Muslims is precisely their inability to read the Qur’an correctly. sadly, this figure reaches 65% of the population of Indonesian Muslims. Jibril's method helps provide solutions to these problems, practical, effective and accurate. Especially when we are dealing with Imams of Mosques and Mushollas, who are not able to read the Qur'an properly and correctly. Keywords: Al-Qur’an, Method Jibril, Santri